2012
DOI: 10.1177/1545109712453854
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Sides: HIV Health Care Practices among Shared Populations of HIV-Positive Latinos Living near the US-Mexico Border

Abstract: Background We compared HIV-positive patients receiving care in the border cities of San Diego, United States, with Tijuana, Mexico. Methods Participants were HIV-positive Latinos (n = 233) receiving antiretroviral therapy (ART) from San Diego– Tijuana clinics (2009-2010). Logistic regression identified correlates of receiving HIV care in San Diego versus Tijuana. Results Those with their most recent HIV visit in San Diego (59%) were more likely to be older, have at least a high school education, and were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…Concern about CAM's effect on adherence and its potential negative interaction with ART (Piscitelli, et al, 2000; Mills, Montori, Perri, Phillips & Koren, 2005) was more common among some Tijuana providers who did not think that their patients used CAM. In contrast with this finding, our earlier work indicates that CAM use is fairly common (67%) among HIV-positive Tijuana patients (Servin, Muñoz, Strathdee, Kozo & Zúñiga, 2012). Integrative medicine is less common in Mexico and provider lack of awareness of patient CAM use may be because it is not currently part of formal physician training which focuses more on evidence-based medicine.…”
Section: Discussioncontrasting
confidence: 78%
“…Concern about CAM's effect on adherence and its potential negative interaction with ART (Piscitelli, et al, 2000; Mills, Montori, Perri, Phillips & Koren, 2005) was more common among some Tijuana providers who did not think that their patients used CAM. In contrast with this finding, our earlier work indicates that CAM use is fairly common (67%) among HIV-positive Tijuana patients (Servin, Muñoz, Strathdee, Kozo & Zúñiga, 2012). Integrative medicine is less common in Mexico and provider lack of awareness of patient CAM use may be because it is not currently part of formal physician training which focuses more on evidence-based medicine.…”
Section: Discussioncontrasting
confidence: 78%
“…Individuals living in the US-Mexico border region, including HIV-positive patients, frequently utilize health services on both sides of the border (Landeck and Garza 2003; Servin et al 2012; Su et al 2011; Zúñiga 2012). The US-Mexico border region is approximately 1969 miles long and is one of the fastest growing regions in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, immigrants are less likely to access or utilize preventive services, especially in areas of cancer screening, STD testing, vaccinations, and pediatric and prenatal preventive care (Echeverria & Carrasquillo, 2006;Goel et al, 2003;Lees et al, 2005;Cohen & Christakis, 2006). Delayed presentation of HIV was also of particular concern among HLI, due to lack of screening and preventive measures (Levy et al, 2007;Servin et al, 2012). As seen among participants in this study, advances in the stages of the disease process that are left undetected can pose serious threats to the health and wellbeing of the community as a whole, while consequently increasing healthcare expenditures.…”
Section: Policymentioning
confidence: 77%
“…Several participants indicated that they received better medical attention, resources and social support for being HIV positive in the U.S. than they did in their home countries. As indicated in the literature, access to better quality health and social services for HIV in the U.S. was a major reason that compelled HLI to remain in the country, despite undocumented and lower socioeconomic status (Servin, Munoz, Strathdee, Kozo & Zuniga, 2012).…”
Section: Accessibility and Healthcare Accessmentioning
confidence: 99%
See 1 more Smart Citation